An algorithm for steganographic embedding of encrypted files in raster images - Ivanova, Yoana (Yearbook Telecommunications, 2022)
The aim of this paper is proposing a method for the application of algorithms for hiding an encrypted file inside of a digital image for cybersecurity purposes. The originality of the method is expressed in the possibility of studying the mathematical algorithms for creating computer graphics. The development of a comprehensive algorithm should contribute to the practical realization of the method proposed. It emphasizes on built-in algorithms in software systems for creating computer graphics and the advantages of steganographic embedding by opensource products that hides any archive file in a digital image. Its application contribution is supported by practical examples of software hiding and archiving an encrypted file in a graphic image.